A research on improvement of almond (P. amygdalus L.) by selection of wild growing types in Tokat Central District - Gercekcioglu R.; Gunes M. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
This study was carried out in 1998-1999 in the Tokat Central District. First 87 sweet almond types were selected from thousands of almond types. Then, according to the method of classification with respect to a weighted scale, 28 types were selected from the 87 almond types and the second year, 8 types were selected from the 28 almond types. All of the selected types have hard shell and are sweet. According to the results of both years in the 8 selected types; the average fruit weights with shell were between 7.58 g (YD-02)-2.18 g (YB-02); kernel weights were between 1.35 g (YD-02)-0.64 g (YD-01); kernel outputs were between 37.16 per cent (YB-02)-17.81 per cent (YD-02); the full kernel ratio was 100.00 per cent in the other types, except for YB-04, ST-11, YD-01 and YB-01. The percentage of double kernels were between 63.33 per cent (YB-02)-3.45 per cent (YD-01).
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)